A novel cryptosystem using DNA sequencing and contextual array splicing system for Medical Internet of Things. (December 2021) - Ugandran, Indumathi; Mahendran, Anand; S., Anandakumar; Hamada, Mohammed; Alnumay, Waleed S.; Ghosh, Uttam; Sharma, Pradip Kumar
Abstract: In the modern world, there is a huge increase in the usage of various technologies which may produce heterogeneous data. Using the latest security algorithms like Triple Data Encryption Standard (TDES), Rivest Shamir Adleman (RSA), Advanced Encryption Standard (AES) these (heterogeneous) data are transferred over the internet. Despite of such good security mechanisms, there exist vulnerabilities to the user data. In the recent years, researchers started the usage of bio-inspired computing models towards security. In this paper, two such bio-inspired computing models namely splicing system and Deoxyribonucleic acid (DNA) sequencing were used. We proposed a novel cryptosystem using contextual array splicing system for DNA sequenced input data. In this process, we have designed Turing machine(s) that perform(s) the conversion of a binary input to DNA sequence and the cryptosystem operation using contextual array splicing system. Next, the developed novel cryptosystem is applied in the domain of Medical Internet of Things (MIoT). Further, we had investigated the proof of correctness. Next, the proposed cryptosystems are proved to be Turing computable. Finally, the security analysis and evaluation of the proposed cryptosystem has been studied.